Primary Peritonitis: An Index Case of Mycoplasma hominis Infection in a Healthy Female - Sabrina Drexel; Daniel Tseng (Case Reports in Surgery)
Introduction. Primary peritonitis in healthy immunocompetent individuals is rare. Several case reports of Streptococcus species causing peritonitis have been described. Here, we present the first case of Mycoplasma hominis as the cause of primary peritonitis in a healthy woman. Case Report. A 42-year-old female with history of uterine fibroids was admitted with abdominal pain and intraperitoneal fluid of unknown etiology. She was initially managed nonoperatively and empirically treated with broad spectrum antibiotics. Blood and urine cultures were unrevealing. Increasing abdominal pain and peritoneal fluid prompted diagnostic laparoscopy which revealed a dense fibrinous exudate covering the entire peritoneal cavity. Peritoneal fluid and biopsies were sent for cytology and culture. The peritoneal fluid was eventually sent for 16 s ribosomal analysis, which discovered Mycoplasma hominis RNA. Her antibiotics were narrowed, and she eventually made a full recovery. Discussion. M. hominis is a rare source of systemic infection but has been known to colonize the urogenital tract and cause localized infections. This is the first presentation of M. hominis causing primary peritonitis in a healthy immunocompetent female. Multidisciplinary management of these patients is critical to achieve a timely diagnosis. Surgical exploration is often unavoidable to rule out secondary peritonitis.